TREE PLANTING ON PUBLIC ROADS AND THE UTILIZATION OF EXOTIC SPECIES: THE DOWNTOWN CASE IN PATO BRANCO/PR - SILVA, Lenir Maristela; HASSE, Ionete; MOCCELIN, Renata; ZBORALSKI, Adriane Rodrigues (Scientia Agraria, 2007)
This objective in this work went identify the arboreal species that compound the tree planting in the downtown area of Pato Branco-PR and a critical discussion about the utilization of exotic species. The trees with were identified individually by the use of a spread sheet to write down the cientific name of the specie, common name, name of the street and the name of the closest common grounds. For the identification of the species they were collected fertile samples that were herborized. Besides, each species was photographed. The data were collected from May to November of 2005. Hey were traveled 31,5 km in thirty four streets. Were identified 3191 arboreal specimens, understanding 47 different species The inventoried area presents the predominance of the specie Ligustrum lucidum W. T. Aiton (62,4%). This specie is not native and it is on the list of invader plants. In the sequence appear Lagerstroemia indica L. (11,4%), Schinus molle L. (6,3%), Bauhinia variegata L. (3,8%), and others (16,1%). From the most abundant species only one is from Brazil (Schinus molle). Framed ad "others" are found varied species but with a very individual frequence lower to 2,95%. From these species, twenty-two are native and twenty-five are exotic. The result demonstrates that the downtown area doesn´t have a peculiar local bioma identity, because, besides there being prevalence of species, more than 60% of the specimens is exotic.